Genetics of Tinnitus: Still in its Infancy - Vona, Barbara; Nanda, Indrajit; Shehata-Dieler, Wafaa; Haaf, Thomas (Frontiers in Neuroscience, 2017)
Tinnitus is the perception of a phantom sound that affects between 10 and 15% of the general population. Despite this considerable prevalence, treatments for tinnitus are presently lacking. Tinnitus exhibits a diverse array of recognized risk factors and extreme clinical heterogeneity. Furthermore, it can involve an unknown number of auditory and non-auditory networks and molecular pathways. This complex combination has hampered advancements in the field. The identification of specific genetic factors has been at the forefront of several research investigations in the past decade. Nine studies have examined genes in a case-control association approach. Recently, a genome-wide association study has highlighted several potentially significant pathways that are implicated in tinnitus. Two twin studies have calculated a moderate heritability for tinnitus and disclosed a greater concordance rate in monozygotic twins compared to dizygotic twins. Despite the more recent data alluding to genetic factors in tinnitus, a strong association with any specific genetic locus is lacking and a genetic study with sufficient statistical power has yet to be designed. Future research endeavors must overcome the many inherent limitations in previous study designs. This review summarizes the previously embarked upon tinnitus genetic investigations and summarizes the hurdles that have been encountered. The identification of candidate genes responsible for tinnitus may afford gene based diagnostic approaches, effective therapy development, and personalized therapeutic intervention.